LANDASAN EPISTIMOLOGIS DALAM PENGEMBANGAN TEORI MANAJEMEN PENDIDIKAN ISLAM - M. Irhas; Kautsar Eka Wardhana; Yusnia Binti Kholifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze and construct epistemological foundations in developing integrative and transformative Islamic education management theory. The paradigmatic complexity in addressing the dichotomy between secular management theories and Islamic worldview becomes the primary focus of this research. The research method employs a qualitative approach with case study strategy involving nine informants consisting of madrasah principals, Islamic education management lecturers, and Islamic educational epistemology experts selected through purposive sampling. Data collection techniques utilize semi-structured in-depth interviews with thematic analysis combined with constant comparative method. Research findings reveal three main dimensions of epistemological foundations: rational, empirical, and revelation-based epistemology integrated within an integrated epistemological framework with four systematic stages: foundation, construction, validation, and implementation. Findings indicate that epistemological construction is circular and integrative, capable of bridging theory-practice dichotomy through triangulated decision making. Implementation faces challenges including change resistance, human resource limitations, and paradigmatic conflicts that can be addressed through integration workshops, gradual change management, capacity building programs, and epistemological dialogue. This research contributes to developing new paradigms of Islamic education management that are authentic, scientific, and applicable through decolonization and Islamization of knowledge processes that can enhance competitiveness and sustainability of Islamic educational institutions in the globalization era